2017
DOI: 10.4254/wjh.v9.i36.1340
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sofosbuvir and ledipasvir in Japanese patients aged 75 years or over with hepatitis C genotype 1

Abstract: AIMTo evaluate the efficacy and safety of a regimen containing sofosbuvir (SOF) and ledipasvir (LDV) in Japanese patients aged ≥ 75 years with hepatitis C genotype 1.METHODSThis multicenter, retrospective study consisted of 246 Japanese patients with HCV genotype 1 at nine centers in Miyazaki prefecture in Japan. Demographic, clinical, virological, and adverse effects (AE)-related data obtained during and after SOF/LDV therapy were collected from medical records. These patients were divided into two groups, yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
4
5
0
Order By: Relevance
“…5,20,28 Additionally, other real-world Japanese studies have shown LDV/SOF to have low frequencies of reported AEs and high SVR12 rates among older patients and those with or without cirrhosis at baseline. 3,16,17 Two notable differences in this study were the ability to assess and constipation, were very low, which is consistent with other real-world LDV/SOF studies conducted in Japan. 16,17 SVR12 results observed were similar and among the highest in comparison with other LDV/SOF studies in the post-marketing setting, ranging from 94% to 99% overall 9,12,13,[15][16][17][18][19]29 and among elderly patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…5,20,28 Additionally, other real-world Japanese studies have shown LDV/SOF to have low frequencies of reported AEs and high SVR12 rates among older patients and those with or without cirrhosis at baseline. 3,16,17 Two notable differences in this study were the ability to assess and constipation, were very low, which is consistent with other real-world LDV/SOF studies conducted in Japan. 16,17 SVR12 results observed were similar and among the highest in comparison with other LDV/SOF studies in the post-marketing setting, ranging from 94% to 99% overall 9,12,13,[15][16][17][18][19]29 and among elderly patients.…”
Section: Discussionsupporting
confidence: 85%
“…3,16,17 Two notable differences in this study were the ability to assess and constipation, were very low, which is consistent with other real-world LDV/SOF studies conducted in Japan. 16,17 SVR12 results observed were similar and among the highest in comparison with other LDV/SOF studies in the post-marketing setting, ranging from 94% to 99% overall 9,12,13,[15][16][17][18][19]29 and among elderly patients. [15][16][17][18]30 If the 97 patients that were missing HCV RNA information after treatment completion were considered as virologic failures, the SVR12 would remain high at 95.59% (95% CI: 94.84%-96.27%), which is also within the range observed in other post-marketing studies of LDV/SOF treatment for HCV GT1 infection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, the efficacy and safety of direct acting antivirals (DAA) in elderly patients has been a topic of interest [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. These are highly effective also in older patients with hepatitis C-related liver disease, comorbidities and concomitant medications causing drug-drug interactions (DDIs) [14,15,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most Japanese patients with hepatitis C are elderly, and those aged ≥70 years account for more than 50% of HCV carriers (7). While new DAA therapies for patients with HCV infection deliver higher cure rates and lower frequencies of adverse events than existing therapies (8), the cost of these drugs is approximately 5-7 million yen ($45,000-64,000) in Japan (9). All patients with HCV infection are considered candidates for DAAs, except for those with shorter life expectancies.…”
mentioning
confidence: 99%